A switch for epitaxial graphene electronics: Utilizing the silicon carbide substrate as transistor channel - Krach, Florian; Hertel, Stefan; Waldmann, Daniel; Jobst, Johannes; Krieger, Michael; Reshanov, S.; Schoner, A.; Weber, Heiko B. (Applied Physics Letters, 2012)
Due to the lack of graphene transistors with large on/off ratio, we propose a concept employing both epitaxial graphene and its underlying substrate silicon carbide (SiC) as electronic materials. We demonstrate a simple, robust, and scalable transistor, in which graphene serves as electrodes and SiC as a semiconducting channel. The common interface has to be chosen such that it provides favorable charge injection. The insulator and gate functionality is realized by an ionic liquid gate for convenience but could be taken over by a solid gate stack. On/off ratios exceeding 44000 at room temperature are found. © 2012 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.2012.nat.dphy.IAP.LAP.aswitc

Bottom-gated epitaxial graphene - Waldmann, Daniel; Jobst, Johannes; Speck, Florian; Seyller, Thomas; Krieger, Michael; Weber, Heiko B. (Nature Materials, 2011)
High-quality epitaxial graphene on silicon carbide (SiC) is today available in wafer size. Similar to exfoliated graphene, its charge carriers are governed by the Dirac-Weyl Hamiltonian and it shows excellent mobilities. For many experiments with graphene, in particular for surface science, a bottom gate is desirable. Commonly, exfoliated graphene flakes are placed on an oxidized silicon wafer that readily provides a bottom gate. However, this cannot be applied to epitaxial graphene as the SiC provides the source material out of which graphene grows. Here, we present a reliable scheme for the fabrication of bottom-gated epitaxial graphene devices, which is based on nitrogen (N) implantation into a SiC wafer and subsequent graphene growth. We demonstrate working devices in a broad temperature range from 6 to 300-K. Two gating regimes can be addressed, which opens a wide engineering space for tailored devices by controlling the doping of the gate structure. © 2011 Macmillan Publishers Limited. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2011.nat.dphy.IAP.LAP.bottom

Charge-carrier transport in large-area epitaxial graphene - Kißlinger, Ferdinand; Popp, Matthias Albert; Jobst, Johannes; Shallcross, Sam; Weber, Heiko B. (Annalen Der Physik, 2017)

Current annealing and electrical breakdown of epitaxial graphene - Hertel, Stefan; Kißlinger, Ferdinand; Jobst, Johannes; Waldmann, Daniel; Krieger, Michael; Weber, Heiko B. (Applied Physics Letters, 2011)
We report on epitaxial graphene on silicon carbide at high current densities. We observe two distinguished regimes, and a final breakdown. First for low current densities the conductance is enhanced due to desorption of adsorbates. Second with increasing bias the sample locally starts to glow and is strongly heated. The silicon carbide material decomposes, graphitic material is formed and thus additional current paths are created. The graphene layer breaks down, which is, however, not visible in high bias data. The final breakdown is a self-amplifying process resulting in a locally destroyed sample but surprisingly with better conductance than the original sample. © 2011 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.2011.nat.dphy.IAP.LAP.curren

Detection of the Kondo effect in the resistivity of graphene: Artifacts and strategies - Jobst, Johannes; Kißlinger, Ferdinand; Weber, Heiko B. (Physical Review B, 2013)
We discuss the difficulties in discovering the Kondo effect in the resistivity of graphene. Similarly to the Kondo effect, electron-electron interaction effects and weak localization appear as logarithmic corrections to the resistance. In order to disentangle these contributions, a refined analysis of the magnetoconductance and the magnetoresistance is introduced. We present numerical simulations which display the discrimination of both effects. Further, we present experimental data of magnetotransport. When magnetic molecules are added to graphene, a logarithmic correction to the conductance occurs, which apparently suggests Kondo physics. Our thorough evaluation scheme, however, reveals that this interpretation is not conclusive: The data can be equally explained by electron-electron interaction corrections in an inhomogeneous sample. Despite our refined analysis, we conclude that additional spectroscopic information will be necessary to unambiguously identify the Kondo effect. © 2013 American Physical Society.
UnivIS-Import:2015-04-14:Pub.2013.nat.dphy.IAP.LAP.detect

Electron-Electron Interaction in the Magnetoresistance of Graphene - Jobst, Johannes; Waldmann, Daniel; Gornyi, Igor; Mirlin, Alexander; Weber, Heiko B. (Physical Review Letters, 2012)
We investigate the magnetotransport in large area graphene Hall bars epitaxially grown on silicon carbide. In the intermediate field regime between weak localization and Landau quantization, the observed temperature-dependent parabolic magnetoresistivity is a manifestation of the electron-electron interaction. We can consistently describe the data with a model for diffusive ( magneto) transport that also includes magnetic-field-dependent effects originating from ballistic time scales. We find an excellent agreement between the experimentally observed temperature dependence of magnetoresistivity and the theory of electron-electron interaction in the diffusive regime. We can further assign a temperature-driven crossover to the reduction of the multiplet modes contributing to electron-electron interaction from 7 to 3 due to intervalley scattering. In addition, we find a temperature-independent ballistic contribution to the magnetoresistivity in classically strong magnetic fields.

Gated Epitaxial Graphene Devices - Waldmann, Daniel; Jobst, Johannes; Speck, Florian; Seyller, Thomas; Krieger, Michael; Weber, Heiko B. (Materials Science Forum, 2012)
A bottom gate scheme is presented to tune the charge density of epitaxial graphene via a gate voltage while leaving the surface open for further manipulation or investigation. Depending on the doping concentration of the buried gate layer, the temperature and illumination, the bottom gate structure can be operated in two regimes with distinct capacitances. A model is proposed, which quantitatively describes the gate operation. The model is verified by a control experiment with an illuminated gate structure using UV light. Using UV illumination the Schottky capacitor (SC) regime, which provides improved gate efficiency, can be used even at low temperatures. © (2012) Trans Tech Publications.
UnivIS-Import:2015-04-14:Pub.2012.nat.dphy.IAP.LAP.gatede
Keywords: Bottom gate; Buried gate; Epitaxial graphene

Gateless patterning of epitaxial graphene by local intercalation - Sorger, Christian; Hertel, Stefan; Jobst, Johannes; Steiner, Christian; Meil, Katharina; Ullmann, Konrad; Albert, A.; Wang, Yabin; Krieger, Michael; Ristein, Jürgen; Maier, Sabine; Weber, Heiko B. (Nanotechnology, 2015)
We present a technique to pattern the charge density of a large-area epitaxial graphene sheet locally without using metallic gates. Instead, local intercalation of the graphene-substrate interface can selectively be established in the vicinity of graphene edges or prede fined voids. It provides changes of the work function of several hundred meV, corresponding to a conversion from n-type to p-type charge carriers. This assignment is supported by photoelectron spectroscopy, scanning tunneling microscopy, scanning electron microscopy and Hall effect measurements. The technique introduces materials contrast to a graphene sheet in a variety of geometries and thus allows for novel experiments and novel functionalities.
UnivIS-Import:2015-04-14:Pub.2015.nat.dphy.IAP.LAP.gatele
Keywords: Graphene; Intercalation; Patterning

Implanted bottom gate for epitaxial graphene on silicon carbide - Waldmann, Daniel; Jobst, Johannes; Fromm, Felix; Speck, Florian; Seyller, Thomas; Krieger, Michael; Weber, Heiko B. (Journal of Physics D-Applied Physics, 2012)
We present a technique to tune the charge density of epitaxial graphene via an electrostatic gate that is buried in the silicon carbide substrate. The result is a device in which graphene remains accessible for further manipulation or investigation. Via nitrogen or phosphor implantation into a silicon carbide wafer and subsequent graphene growth, devices can routinely be fabricated using standard semiconductor technology. We have optimized samples for room temperature as well as for cryogenic temperature operation. Depending on implantation dose and temperature we operate in two gating regimes. In the first, the gating mechanism is similar to a MOSFET, the second is based on a tuned space charge region of the silicon carbide semiconductor. We present a detailed model that describes the two gating regimes and the transition in between. © 2012 IOP Publishing Ltd.
UnivIS-Import:2015-04-14:Pub.2012.nat.dphy.IAP.LAP.implan

Origin of logarithmic resistance correction in graphene - Jobst, Johannes; Weber, Heiko B. (Nature Physics, 2012)
Chen et al.1 recently presented data of a logarithmic low-temperature anomaly in the resistance of graphene flakes and attributed this to Kondo physics. The samples were irradiated beforehand with ions, and the appearance of a logarithmic anomaly was linked to the presence of induced defect states with unpaired electrons. Here, we present evidence that this assignment to Kondo physics is wrong. The observed effect is due to electron–electron interaction (EEI)2, which in the diffusive regime also gives a logarithmic correction to the resistance (in two dimensions). It is an effect that is based on very general assumptions, and that has been observed in many two-dimensional materials in excellent agreement with theory. It has been pinpointed in graphene recently3.

Quantum oscillations and quantum Hall effect in epitaxial graphene - Jobst, Johannes; Waldmann, Daniel; Speck, Florian; Hirner, R.; Maude, Duncan; Seyller, Thomas; Weber, Heiko B. (Physical Review B, 2010)
We investigate the transport properties of high-quality single-layer graphene, epitaxially grown on a 6H-SiC(0001) substrate. We have measured transport properties, in particular charge-carrier density, mobility, conductivity, and magnetoconductance of large samples as well as submicrometer-sized Hall bars which are entirely lying on atomically flat substrate terraces. The results display high mobilities, independent of sample size. The temperature dependence of the conductance indicates a rather strong coupling to the SiC substrate. An analysis of the Shubnikov-de Haas effect yields the Landau-level spectrum of single-layer graphene. When gated close to the Dirac point, the mobility increases substantially and the graphenelike quantum Hall effect occurs.

Quasi-freestanding Graphene on SiC(0001) - Speck, Florian; Ostler, Markus; Röhrl, Jonas; Jobst, Johannes; Waldmann, Daniel; Hundhausen, Martin; Ley, Lothar; Weber, Heiko B.; Seyller, Thomas (Materials Science Forum, 2010)
We report on a comprehensive study of the properties of quasi-freestanding monolayer and bilayer graphene produced by conversion of the (6√3×6√3)R30° reconstruction into graphene via intercalation of hydrogen. The conversion is confirmed by photoelectron spectroscopy and Raman spectroscopy. By using infrared absorption spectroscopy we show that the underlying SiC(0001) surface is terminated by hydrogen in the form of Si-H bonds. Using Hall effect measurements we have determined the carrier concentration and type as well as the mobility which lies well above 1000 cm2/Vs despite a significant amount of short range scatterers detected by Raman spectroscopy. © (2010) Trans Tech Publications.
UnivIS-Import:2015-04-14:Pub.2010.nat.dphy.IAP.LAP.quasif
Keywords: ARPES; Graphene; Hydrogen; Infrared absorption spectroscopy; Intercalation; Raman spectroscopy; XPS

Raman spectroscopy and electrical transport studies of free-standing epitaxial graphene: Evidence of an AB-stacked bilayer - Shivaraman, Shriram; Jobst, Johannes; Waldmann, Daniel; Weber, Heiko B.; Spencer, Michael (Physical Review B, 2013)
We fabricate free-standing graphene structures from epitaxial graphene on silicon carbide using a photoelectrochemical (PEC) etching process. A combination of Raman spectroscopy and magnetotransport measurements was used to investigate multiterminal devices in various geometries. From the analysis of Raman data and Shubnikov-de Haas oscillations, we conclude that the buffer layer is converted into a graphene layer and, thus, monolayer graphene on SiC gets converted to a free-standing AB-stacked bilayer. The bilayer exhibits inversion-symmetry breaking because of differential doping between the layers. Additionally, lateral inhomogeneities exist in the form of domains with nonuniform mobility. The same PEC process on a pure buffer layer, however, does not yield monolayer graphene.

Robust graphene membranes in a silicon carbide frame - Waldmann, Daniel; Butz, Benjamin; Bauer, Sebastian; Englert, Jan; Jobst, Johannes; Ullmann, Konrad; Fromm, Felix; Ammon, Maximilian Michael; Enzelberger-Heim, Michael; Hirsch, Andreas; Maier, Sabine; Schmuki, Patrik; et al. (ACS nano, 2013)
We present a fabrication process for freely suspended membranes consisting of bi- and trilayer graphene grown on silicon carbide. The procedure, involving photoelectrochemical etching, enables the simultaneous fabrication of hundreds of arbitrarily shaped membranes with an area up to 500 μm(2) and a yield of around 90%. Micro-Raman and atomic force microscopy measurements confirm that the graphene layer withstands the electrochemical etching and show that the membranes are virtually unstrained. The process delivers membranes with a cleanliness suited for high-resolution transmission electron microscopy (HRTEM) at atomic scale. The membrane, and its frame, is very robust with respect to thermal cycling above 1000 °C as well as harsh acidic or alkaline treatment.

Tailoring the graphene/silicon carbide interface for monolithic wafer-scale electronics - Hertel, Stefan; Waldmann, Daniel; Jobst, Johannes; Albert, Andreas; Albrecht, Matthäus; Krieger, Michael; Reshanov, Sergey; Schöner, Adolf; Weber, Heiko B. (Nature Communications, 2012)
Graphene is an outstanding electronic material, predicted to have a role in post-silicon electronics. However, owing to the absence of an electronic bandgap, graphene switching devices with high on/off ratio are still lacking. Here in the search for a comprehensive concept for wafer-scale graphene electronics, we present a monolithic transistor that uses the entire material system epitaxial graphene on silicon carbide (0001). This system consists of the graphene layer with its vanishing energy gap, the underlying semiconductor and their common interface. The graphene/semiconductor interfaces are tailor-made for ohmic as well as for Schottky contacts side-by-side on the same chip. We demonstrate normally on and normally off operation of a single transistor with on/off ratios exceeding 10(4) and no damping at megahertz frequencies. In its simplest realization, the fabrication process requires only one lithography step to build transistors, diodes, resistors and eventually integrated circuits without the need of metallic interconnects.

The quasi-free-standing nature of graphene on H-saturated SiC(0001) - Speck, Florian; Jobst, Johannes; Fromm, Felix; Ostler, Markus; Waldmann, Daniel; Hundhausen, Martin; Weber, Heiko B.; Seyller, Thomas (Applied Physics Letters, 2011)
We report on an investigation of quasi-free-standing graphene on 6H-SiC(0001) which was prepared by intercalation of hydrogen under the buffer layer. Using infrared absorption spectroscopy, we prove that the SiC(0001) surface is saturated with hydrogen. Raman spectra demonstrate the conversion of the buffer layer into graphene which exhibits a slight tensile strain and short range defects. The layers are hole doped (p 5.0 - 6.5 1012 cm -2) with a carrier mobility of 3100 cm2/Vs at room temperature. Compared to graphene on the buffer layer, a strongly reduced temperature dependence of the mobility is observed for graphene on H-terminated SiC(0001) which justifies the term quasi-free-standing. © 2011 American Institute of Physics.
UnivIS-Import:2015-03-09:Pub.2011.nat.dphy.IAP.exphys.thequa

Towards wafer-size graphene layers by atmospheric pressure graphitization of silicon carbide - Emtsev, Konstantin; Bostwick, A.; Horn, Karsten; Jobst, Johannes; Kellogg, Gary L.; Ley, Lothar; McChesney, J.; Ohta, T.; Reshanov, Sergey; Röhrl, Jonas; Rotenberg, E.; Schmid, A.; et al. (Nature Materials, 2009)
Graphene, a single monolayer of graphite, has recently attracted considerable interest owing to its novel magneto-transport properties, high carrier mobility and ballistic transport up to room temperature. It has the potential for technological applications as a successor of silicon in the post Moore's law era, as a single-molecule gas sensor, in spintronics, in quantum computing or as a terahertz oscillator. For such applications, uniform ordered growth of graphene on an insulating substrate is necessary. The growth of graphene on insulating silicon carbide (SiC) surfaces by high-temperature annealing in vacuum was previously proposed to open a route for large-scale production of graphene-based devices. However, vacuum decomposition of SiC yields graphene layers with small grains (30-200 nm; refs 14-16). Here, we show that the ex situ graphitization of Si-terminated SiC(0001) in an argon atmosphere of about 1 bar produces monolayer graphene films with much larger domain sizes than previously attainable. Raman spectroscopy and Hall measurements confirm the improved quality of the films thus obtained. High electronic mobilities were found, which reach =2,000 cm 2 V 1 s 1 at T=27 K. The new growth process introduced here establishes a method for the synthesis of graphene films on a technologically viable basis.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.IAP.LAP.towwar

Transport properties of high-quality epitaxial graphene on 6H-SiC(0001) - Jobst, Johannes; Waldmann, Daniel; Speck, Florian; Hirner, R.; Maude, Duncan; Seyller, Thomas; Weber, Heiko B. (Solid State Communications, 2011)
We have extensively studied the electronic properties of epitaxial graphene grown on the Si face of a 6H silicon carbide substrate by thermal decomposition in an argon atmosphere. Using e-beam lithography, large van der Pauw structures as well as Hall bars were patterned. Their size ranged from millimeters down to submicrometer-sized Hall bars, the latter entirely placed on atomically flat substrate terraces. We found reproducible electronic properties, independent of the sample size and orientation, over a broad temperature range. A comparison of the mobility values indicated no enhanced scattering at the macroscopic step edges of the SiC substrate and due to adsorbed molecules. However, the strong coupling to the substrate results in an elevated charge carrier density n and a reduced mobility mu compared to exfoliated graphene. If n is decreased the mobility rises substantially (up to 29 000 cm(2)/V s at 25 K), and Shubnikov-de Haas oscillations and the graphene-like quantum Hall effect become visible. This leads to the conclusion that the electrons in epitaxial graphene have the same quasi-relativistic properties previously shown in exfoliated graphene and expected from theory. (C) 2011 Elsevier Ltd. All rights reserved.